2006
DOI: 10.1189/jlb.1005581
|View full text |Cite
|
Sign up to set email alerts
|

Systemic suppression of interferon-γ responses in Buruli ulcer patients resolves after surgical excision of the lesions caused by the extracellular pathogen Mycobacterium ulcerans

Abstract: Buruli ulcer (BU), caused by Mycobacterium ulcerans, is the third most common mycobacterial infection in immunocompetent humans besides tuberculosis and leprosy. We have compared by ex vivo enzyme-linked immunospot analysis interferon-gamma (IFN-gamma) responses in peripheral blood mononuclear cells (PBMC) from BU patients, household contacts, and individuals living in an adjacent M. ulcerans nonendemic region. PBMC were stimulated with purified protein derivative (PPD) and nonmycobacterial antigens such as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 40 publications
4
51
1
Order By: Relevance
“…We have recently confirmed this finding on primary T cells using human peripheral blood CD4 + T lymphocytes and have shown that the effects of mycolactone are not restricted to IL-2, since it blocked the activation-induced production of IFN-g, IL-4, IL-17, IL-10, TNF, IL-8, and MIP-1b (15). Several independent studies have reported defective systemic production of IFN-g in patients with active ulcers (16)(17)(18)(19)(20). Our recent multiplex analysis of the immunological profile of BUD patients showed that the production of several other Th1, Th2, and Th17 cytokines was altered.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…We have recently confirmed this finding on primary T cells using human peripheral blood CD4 + T lymphocytes and have shown that the effects of mycolactone are not restricted to IL-2, since it blocked the activation-induced production of IFN-g, IL-4, IL-17, IL-10, TNF, IL-8, and MIP-1b (15). Several independent studies have reported defective systemic production of IFN-g in patients with active ulcers (16)(17)(18)(19)(20). Our recent multiplex analysis of the immunological profile of BUD patients showed that the production of several other Th1, Th2, and Th17 cytokines was altered.…”
supporting
confidence: 53%
“…These cellular response defects were independent of the activation stimulus. Moreover, they resolved after surgical excision of the lesions or antibiotic treatment, demonstrating their association with the presence of bacteria ( [20][21][22][23]. In experimentally infected animals, mycolactone has been shown to diffuse from cutaneous lesions and to gain access to the mononuclear cells of peripheral blood and lymphoid organs (24).…”
mentioning
confidence: 99%
“…In fact, the antibiotic administration has been shown to increase phagocytosis of bacilli at the infection foci and to promote inflammatory cellular responses (66), associated with an increased production of IFN-g (67), which can be related to the reduction of mycolactone concentrations, allowing macrophage activation and further containment of the infection. Accordingly, it has been reported that after the surgical excision of BU lesions, the IFN-g production is increased (68). IFN-g may also be involved in the spontaneous healing of lesions that occurs in BU patients (3,23).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Furthermore, BU disease leads to reduced interferon (IFN)-γ release. 27 Management of HIV/AIDS over the years has seen progressive improvement in drug therapy and clearer guidelines, which has dramatically decreased mortality and incidence of AIDSdefining opportunistic infections. 28,29 Despite this breakthrough 30 In the presence of a treated or ongoing opportunistic infection such as TB, such paradoxical IRIS could occur in which case it would be defined as 1) a new, worsening or recurrent sign or symptom consistent with an exaggerated or atypical inflammatory reaction to the previously diagnosed opportunistic infection, 2) the exclusion of medication toxicity or other disease processes as the cause of the abnormal event, and 3) a supportive evidence be it by some specialized imaging or histopathology.…”
Section: Introductionmentioning
confidence: 99%